6-Year Results of CNV Secondary to Pathological Myopia Treated with Ranibizumab - Hefner, L.; Gerding, H. (Klinische Monatsblätter für Augenheilkunde, 2017)
Background The current standard treatment of choroidal neovascularisation (CNV) secondary to pathological myopia (PM) is intravitreal injection of VEGF antagonists. We now present our 6-year results after treating patients with CNV secondary to PM with ranibizumab. Patients and Methods We retrospectively analysed 15 treatment-naive eyes of 13 patients (10 women, 3 men, mean age 59.2; standard deviation (SD) 11.1; range 41–78 years) with visual impairment related to CNV secondary to PM, who were treated with at least 1 injection of ranibizumab. Follow-up treatments were indicated according to our PRN (pro re nata) regimen. Re-treatment criteria were: reduction in visual acuity and/or activity in OCT or fluorescence angiography. Results Patients received a mean of 3.5 ranibizumab injections (SD 3.4; range 1–12) during a mean follow-up of 85 months (SD 6.6; range 76–102 months). Initial spherical equivalent was − 12.4 ± 4.0 dpt (range − 7.5 to 20.5 dpt). Baseline visual acuity was (log MAR) 0.65 ± 0.28. After one month, visual acuity improved to 0.43 ± 0.23 (p = 0.002), after 3 months to 0.38 ± 0.22 (p = 0.002), after 6 months to 0.34 ± 0.22 (p = 0.002) and after 9 months to 0.35 ± 0.23 (p = 0.002). After 1 year, visual acuity was 0.35 ± 0.24 (p = 0.001), after 2 years 2 0.35 ± 0.23 (p = 0.001), after 3 years 0.35 ± 0.23 (p = 0.002), after 4 years 0.37 ± 0.23 (p = 0.002), after 5 years 0.38 ± 0.23 (p = 0.002), and after 6 years 0.39 ± 0.26 (p = 0.016). Conclusion After considerable initial improvement in visual acuity, the initial gain was maintained by a strict PRN regimen for the observation and treatment of patients with neovascular membranes secondary to pathological myopia. The number of injections needed to achieve stable visual acuity was lower than with other diseases that respond to anti-VEGF.
Keywords: pathological myopia; choroidal neovascularisation; anti-VEGF; ranibizumab